Analysis of Evaluation of Grade IV Students' Understanding in Paragraph Writing at SDN 158 Palembang - Mardiah Astuti; Bella Graceva Canavallia; Padiman Padiman; Selvia Ananta; Shinta Bela (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aims to analyze the understanding of grade IV students in writing paragraphs, including obstacles and errors that often occur. This study uses a qualitative approach with an in-depth exploration design of the paragraph writing process. The research subjects consisted of grade IV students, who were selected to describe their writing abilities at the primary education stage. Data collection techniques involve direct observation, in-depth interviews, and documentation, allowing researchers to obtain rich and comprehensive data. Data analysis is carried out through coding techniques to facilitate information grouping, pattern identification, and drawing valid conclusions. The results of the study are expected to provide an overview of students' level of understanding of the structure and rules of paragraph writing, the factors that affect their difficulties, and the role of teachers in helping students overcome these obstacles. This research is expected to be a reference for educators in designing more effective learning strategies to improve students' writing skills at the elementary level.